2021
DOI: 10.1002/cam4.4102
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of vessels encapsulating tumor clusters in treatment optimization for recurrent early‐stage hepatocellular carcinoma

Abstract: Background The predictive value of vessels encapsulating tumor clusters (VETC) in recurrent early‐stage hepatocellular carcinoma (HCC) remains unclear. Therefore, the aim of the present study was to investigate the prognostic significance of VETC in patients with recurrent early‐stage HCC after repeat hepatic resection (RHR) or radiofrequency ablation (RFA). Methods From December 2005 to December 2016, 138 patients receiving RHR and 188 patients receiving RFA were recruited. VETC was evaluated by immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…7 In addition, VETC pattern may represent a reliable marker for selecting recurrent early-stage HCC patients who may benefit from repeat hepatic resection. 8 Notably, it is suggested that the VETC pattern is associated with the effect of sorafenib treatment for HCC patients. Vessels that encapsulate tumor cluster-positive HCC patients may have a better prognosis than that of VETC-negative HCC patients when treated with sorafenib.…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, VETC pattern may represent a reliable marker for selecting recurrent early-stage HCC patients who may benefit from repeat hepatic resection. 8 Notably, it is suggested that the VETC pattern is associated with the effect of sorafenib treatment for HCC patients. Vessels that encapsulate tumor cluster-positive HCC patients may have a better prognosis than that of VETC-negative HCC patients when treated with sorafenib.…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen total studies, incorporating 2597 total patients (1203 in the RHR group versus 1394 in the RFA group), were deemed eligible for inclusion in the final data analysis ( Figure 1 ) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. The majority of studies originated from East Asia (nine studies from China, three from Japan, one from Singapore, two from Taiwan and one from Korea), while one study was an international multicenter study.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding patient inclusion criteria, absence of extrahepatic spread, presence of intrahepatic HCC recurrence at a site distant from the original tumor and Child-Turcotte-Pugh (CTP) scores A or B were uniformly reported among the included studies. With respect to employed tumor number and size cut-offs, two studies [ 25 , 32 ] reported inclusion of patients with up to three tumors with a 3 cm size cut-off, while another two studies used 5 cm [ 38 ] and 6 cm cut-offs [ 36 ]. One study reported inclusion of BCLC stage 0 or A patients [ 31 ] and four studies adhered to the Milan criteria for size and number of tumors [ 23 , 24 , 30 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations